Enhanced Control by Visualisation of Process Characteristics : Video Monitoring of Coal Powder Injection in a Blast Furnace - Daoud, Jihad; Nipl, Igor (2000)
This master thesis, based on work performed at Luleå University of Technology in cooperation with Mefos, is about measurement of pulverised coal flow injected into a blast furnace, compensating for some of the usually used coke. Coal is drawn from an injection vessel and transported under pressure with the help of nitrogen gas to a blast furnace. It is blown through pipes to the tuyeres where it is injected into the iron making process. Irregular coal supply to the furnace has bad influence on the quality of the produced iron so reliable control is needed. In controlling the flow, it is of great importance that the on-line flow measurement is accurate. Enhancing the existing measurement would be beneficial for the quality of the produced iron. Therefore new means of blast furnace process surveillance and flow measurement, using cameras and image processing, are studied. The idea behind camera surveillance is also beneficial for estimation of other process parameters. The main goal is obtaining relevant information from image data in order to estimate the pulverised coal flow. Methods for achieving this are investigated and discussed. A comparison to old measurement data is made. Also validation of data retrieved with the help of image processing is mentioned. It has been shown that video monitoring in conjunction with image processing is a feasible option when it comes to coal flow estimation. The images include potential information for other purposes like determining the temperature of the flame and how well the coal is distributed inside the blast furnace. This would solve some of the problems and eliminate obstacles caused by the nature of the steel making process. Validerat; 20101217 (root)